2015
DOI: 10.1371/journal.pone.0144240
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Novel Decellularized Fibrocartilage “Book” Scaffold for Use in Tissue Engineering

Abstract: At the tendon-to-bone insertion, there is a unique transitional structure: tendon, non-calcified fibrocartilage, calcified fibrocartilage, and bone. The reconstruction of this special graded structure after defects or damage is an important but challenging task in orthopedics. In particular, reconstruction of the fibrocartilage zone has yet to be successfully achieved. In this study, the development of a novel book-shape scaffold derived from the extracellular matrix of fibrocartilage was reported. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Another limitation to preparing D‐BFT composites is that fibrocartilage presents low vascularity and lacks direct cell–cell connections, allowing for solution infiltration of few chemicals. Triton‐X100 and SDS are typically used in existing protocols for preparing tendon‐to‐bone composites or for fibrocartilage decellularization . However, the decellularized tendon‐to‐bone composites did not assess their bio‐components, structures, biocompatibility, and ability to repair bone defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation to preparing D‐BFT composites is that fibrocartilage presents low vascularity and lacks direct cell–cell connections, allowing for solution infiltration of few chemicals. Triton‐X100 and SDS are typically used in existing protocols for preparing tendon‐to‐bone composites or for fibrocartilage decellularization . However, the decellularized tendon‐to‐bone composites did not assess their bio‐components, structures, biocompatibility, and ability to repair bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the boundary between the tendon and bone was still observed after 16 weeks . Moreover, to date, few methods are available for thoroughly removing cells from the enthesis scaffold or decellularization of the whole composite . Recently, Xu et al developed several protocols for preparing porcine Achilles tendon to bone composite.…”
Section: Introductionmentioning
confidence: 99%
“…The quanti cations of DNA in the decellularized book-shaped enthesis scaffolds were performed using DNeasy Blood & Tissue protocol according to the manufacturer's instructions [12]. Speci cally, the decellularized book-shaped enthesis scaffolds (N=3) were weighed and minced after freeze-dried for 24 h using a lyophilizer (SIM International Group, USA).…”
Section: Dna Content Analysis and Mechanical Testsmentioning
confidence: 99%
“…With the development of tissue engineering technology, decellularized bioscaffolds have received great attention due to their ability to enhance tissue regeneration and repair damaged tissues [10][11][12]. Previous studies indicated that organ-speci c extracellular matrix scaffolds derived from site-speci c homologous tissues may be better suited for constructive tissue remodeling than no site-speci c tissue sources.…”
Section: Introductionmentioning
confidence: 99%
“…Being freed of cells and cellular components, these scaffolds produce minute antigenicity [2,6,9] and provide a biologic environment for cellular ingrowth and subsequent remodelling. However, there is a lack of morphologic and functional data on how exactly the commonly used methods of acellularisation impact extracellular matrix integrity, including commonly used chemical and physical protocols [3,10].…”
Section: Introductionmentioning
confidence: 99%